2017
DOI: 10.15376/biores.12.3.4627-4638
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biogas Yield of Chinese Herbal Medicine Extraction Residue by Hydrothermal Pretreatment

Abstract: aChinese herbal medicine extraction residue (CHER) is a special organic waste produced in China. Because of the high content of lignocelluloses, CHER have a weak bioconversion efficiency for bio-products production. This study investigates the effect of a hydrothermal pretreatment (HTP, 140 to 220 °C, 15 min) on the organic matter solubilisation, biochemical methane potential, and methanation kinetics of CHER during anaerobic digestion (AD). The AD test was conducted with 5 g/L total solid at 35 °C for 30 d. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, there is a dearth of research into effective HER utilization. Hitherto, the reutilization of these resources has tended to focus on the re-extraction of other ingredients or conversion to animal feedstuff ( Li et al, 2014 ; Wang et al, 2017 ). Several studies have reported that HER can be used as culture media for microbe fermentation and stimulate the production of extracellular enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a dearth of research into effective HER utilization. Hitherto, the reutilization of these resources has tended to focus on the re-extraction of other ingredients or conversion to animal feedstuff ( Li et al, 2014 ; Wang et al, 2017 ). Several studies have reported that HER can be used as culture media for microbe fermentation and stimulate the production of extracellular enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In rural areas, especially in developing countries such as Brazil, (PINAS et al 2018); Chile (RODRIGUEZ-MONROY et al 2018); China (WANG et al 2017); India (RAYCHAUDHURI & GHOSH, 2016) and Pakistan (MIRZA et al 2008) there is a great variety of lignocellulosic biomass that has reasonable potential for energy production by means anaerobic digestion, for instance cattle manure. Nevertheless, cattle manure can yield low biogas production since it has lignocellulosic structures of low degradability rate (VANHOLME et al 2010).…”
Section: Introductionmentioning
confidence: 99%